A Case of Pregnancy with Ebsteins Anomaly - Ruman, Umme; Chowdhury, Tanzeem Sabina; Maherunnessa, -; Sultana, Rebeka; Nargis, Sohelee (BIRDEM Medical Journal, 2016)
26- years old multigravida ,developed palpitation and dizziness at 30th gestational weeks and was got admitted in BIRDEM hospital. Her ECG showed ST-depression (anteriors) .Echocardiogram revealed severe atrialized right ventricle, non-restrictive ASD secundum. She was diagnosed as a case of pregnancy with Ebsteins anomaly with ASD. At 34th gestational week, she underwent spontaneous pre-term labour and gave birth to a still born. She developed peripheral cyanosis during pregnancy which subsided few days after delivery. Birdem Med J 2015; 5(1): 46-49